Determination of the pedagogical conditions for forming the readiness of future primary school teachers - Zhakipbekova, Saule (Opción, 2018)
An article dealt with the questions of training of pedagogical personnel for work in inclusive educational institutions. The actual direction in meeting the challenges for forming the readiness of pedagogical potential is determination of pedagogical conditions at the higher school, development of learning technologies, aimed at bridging the gap between theoretical knowledge and professional skills and abilities of the future primary school teacher. Also, there is determined a role of pedagogical conditions at realization of model for forming the readiness that will allow to carry out the training process effectively of future primary school teachers for joint training of children with special educational needs.